“NO TE VOY A DEJAR NUNCA” – CULTURE AND SECOND LANGUAGE ACQUISITION FOR SURVIVAL IN FEAR THE WALKING DEAD - Nuruddin, Sharon M. (Dialogue, 6(3), 2019)
Popular culture reinforces and shapes the beliefs and values of the individual, the community, and the masses. It can also transmit hidden messages about aspects of human behavior that are reiterated in scholarly research. In the field of education, particularly in world language teacher education, film and television can be used as an effective tool for examining how we acquire a second language. Using a symbolic convergence theory perspective (SCT) (Bormann, 1972), I employ Sellnow’s (2014) three-step process for the rhetorical analyses of mediated popular culture texts to reveal “covert messages” (p. 9) within the popular American Movie Channel (AMC) television series, Fear the Walking Dead (FTWD). These messages inform how second language and culture acquisition develop and serve as life-saving resources in extreme cases of cultural and linguistic isolation. In Season 1 of FTWD, Nicholas “Nick” Clark, embarks on an unintentional language and cultural immersion trip to Mexico. His experience reflects research on second language and culture acquisition, reinforcing the understanding that languages can be learned rapidly when it is a matter of survival. My analysis will show that while language learning can transpire through a formally-structured classroom experience, it can also transpire informally—through a Vygotskian (1978), sociocultural, “survivalist” language and culture learning experience—as reflected in FTWD. Applying Sellnow’s process and Bormann’s perspective can help teacher educators and their students find deeper meaning through new and engaging popular culture texts. Keywords: Fear the Walking Dead, zombies, second language acquisition, teacher education, Spanish language teaching, popular culture, survivalist language learning, symbolic convergence theory, rhetorical analysis, zone of proximal development
Keywords: Type of access: Open Access